KEBIJAKAN PEMERINTAH ACEH BARAT DALAM MENGANTISIPASI ALIRAN SESAT DAN PEMURTADAN - Fachrur Rizha (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
This research discusses phonemena silting aqidah that occurred in West Aceh district and government role in determining policy in anticipating effort dissemination of heresy and apostasy that happened in society society. The research method using qualitative method with descriptive approach. The subjects of the study were those who were involved in the settlement of cases of heresy and apostasy in the District of West Aceh. The object of research is matters relating to the government's policy in tackling the heresy in West Aceh District. The result of the research shows that in the tackling of heresy and apostasy, the Government of West Aceh District has conducted a number of policies and efforts, among others: guidance of public aqidah, reviving the ta'lim assembly and maghrib to study, forming forum of acceleration of Islamic law enforcement, and designing the village reusam. In the effort to solve every case of heresy and apostasy, the government also prioritizes persuasive communication and dialogue by involving related institutions and society.